2017
DOI: 10.1371/journal.pone.0168881
|View full text |Cite
|
Sign up to set email alerts
|

Bubble-Induced Endothelial Microparticles Promote Endothelial Dysfunction

Abstract: Decompression sickness is a systemic pathophysiological process caused by bubbles and endothelial microparticles (EMPs) are established markers reflecting competency of endothelial function and vascular biology. Here, we investigated the effects of bubble-induced EMPs on endothelial cells in vitro and vivo. Rat pulmonary microvascular endothelial cells (PMVECs) were isolated and stimulated by bubbles and bubble-induced EMPs were collected and incubated with normal PMVECs in vitro. Cell viability and apoptosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 32 publications
(36 reference statements)
1
20
0
Order By: Relevance
“…The endothelium plays a key role in response to bubble contact, which convert it from inactivated to activated condition, resulting in endothelial dysfunction and mediating deleterious effects upon the surrounding tissues. Previous studies demonstrated that bubble contact promoted MPs formation, which further facilitated endothelial dysfunction [25-27, 30]. An illustration of the mechanisms involved in bubble-induced EMPs formation is meaningful because it may provide an innovative perspective for preventing adverse effects of bubble-induced EMPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The endothelium plays a key role in response to bubble contact, which convert it from inactivated to activated condition, resulting in endothelial dysfunction and mediating deleterious effects upon the surrounding tissues. Previous studies demonstrated that bubble contact promoted MPs formation, which further facilitated endothelial dysfunction [25-27, 30]. An illustration of the mechanisms involved in bubble-induced EMPs formation is meaningful because it may provide an innovative perspective for preventing adverse effects of bubble-induced EMPs.…”
Section: Discussionmentioning
confidence: 99%
“…HUVECs were then subjected to 30 min of bubble contact as previously described and non-treated cells were used as controls. In brief, half of one milliliter nitrogen (N 2 ) was injected to CO 2 -independent medium and the device was put into a 37 °C shaking table so that bubbles were allowed to contact with the confluent cells [30]. Six hours after bubble stimulus, the cultural medium was collected and cleared of cells and cell debris by centrifugation at 1500 g for 15 min at 4℃.…”
Section: Methodsmentioning
confidence: 99%
“…Bubble-induced MPs may only occupy a section of all MPs after DCS. Other factors such as an inflammatory response may also activate the endothelium and subsequently induce MP release (Yu et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial dysfunction is likely a key contributor to the pathophysiology of DCI. Bubble contact with endothelial cells released microparticles which decreased cell viability, increased apoptosis, and caused over-expression of pro-inflammatory cytokines (Yu et al, 2017 ). Protection of the endothelium with escin (the main active compound in horse chestnut seed extract) reduced the incidence of DCI in the rat (Zhang et al, 2017a ).…”
Section: Compatibility Of Ahs With Decompression From Divingmentioning
confidence: 99%